2013
DOI: 10.1117/1.jbo.18.1.016007
|View full text |Cite
|
Sign up to set email alerts
|

Depth probing of diffuse tissues controlled with elliptically polarized light

Abstract: Abstract. Polarization gating is a popular technique in biomedical optics. It is widely used to inspect the surface of the tissues (under colinear or cocircular detection) or instead to probe the volume (cross-linear detection), without information on the probed depth. Elliptical polarization is introduced to explore the possibility of probing diffuse tissues at selective depths. A thorough Monte Carlo simulation study shows complete correlation between the probed depths and the ellipticity of the polarized li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 16 publications
(18 reference statements)
0
33
1
Order By: Relevance
“…3 where the interrogation depth for the linearly polarized signal was determined to be τ ~3. Linear relationships between probing depth and ellipticity were also observed in imaging experiments performed by Da Silva et al [37] and in results obtained in single wavelength Monte Carlo simulations by Rehn et al [23]. However, our results demonstrate that alterations in spectroscopic features can be extracted by tuning the ellipticity in EPRS in highly scattering media.…”
Section: Depth-resolved Spectroscopycontrasting
confidence: 44%
See 1 more Smart Citation
“…3 where the interrogation depth for the linearly polarized signal was determined to be τ ~3. Linear relationships between probing depth and ellipticity were also observed in imaging experiments performed by Da Silva et al [37] and in results obtained in single wavelength Monte Carlo simulations by Rehn et al [23]. However, our results demonstrate that alterations in spectroscopic features can be extracted by tuning the ellipticity in EPRS in highly scattering media.…”
Section: Depth-resolved Spectroscopycontrasting
confidence: 44%
“…In an alternative method, our group and others have developed a simple linear polarization gating to isolate tissue signals originating from shallow depths in tissues from the diffuse background of the underlying stroma using spectroscopic and imaging setups [13][14][15][16][17][18][19][20][21]. In polarization gated spectroscopy and imaging, polarized photons maintain their incident polarization for a particular number of mean free paths (MFP) depending on density of optical scatterers and their properties such as anisotropy factor [22,23]. In linear polarization gating, a sample is illuminated with a linear polarized light and two components of the scattered light are detected: the co-polarized signal with its polarizations parallel to the incident polarization (I ║ ) and the cross-polarized signal with its polarization orthogonal to the incident light (I^).…”
Section: Introductionmentioning
confidence: 99%
“…This effect was further investigated and verified by Monte Carlo simulations in a semi-infinite medium. 20 The simulation results concluded that the mean visitation depth for linearly polarized light [∼2 mean free paths (MFPs)] is smaller than that of circularly polarized light (∼10 MFPs). They also found that elliptical polarization can be tuned between linear and circular polarization to reach different penetration depths.…”
Section: Introductionmentioning
confidence: 99%
“…In biological tissues, within the range of 600-1000 nm, the reduced scattering coefficient is greater than the absorption coefficient which is true in this study (0.25/0.015 E17). It is true that it is easier to work with tissue-like phantom with known optical properties [35,36]. However, we felt (c) Representative photographs of the tissue before and 50 min after application of OCA.…”
Section: Sample and Mediummentioning
confidence: 97%
“…Recently, Da Silva et al reported the use of polarization gating imaging with elliptically polarized light [35,36]. They demonstrated the possibility of imaging differential tissue depths as a function of the polarization ellipticity.…”
Section: Introductionmentioning
confidence: 97%